Experimental and Computational Tools for Analysis of Signaling Networks in Primary Cells. (4th February 2014) - Schoof, Erwin M.; Linding, Rune
Abstract: Cellular information processing in signaling networks forms the basis of responses to environmental stimuli. At any given time, cells receive multiple simultaneous input cues, which are processed and integrated to determine cellular responses such as migration, proliferation, apoptosis, or differentiation. Protein phosphorylation events play a major role in this process and are often involved in fundamental biological and cellular processes such as protein‐protein interactions, enzyme activity, and immune responses. Determining which kinases phosphorylate specific phospho sites poses a challenge; this information is critical when trying to elucidate key proteins involved in specific cellular responses. Here, methods to generate high‐quality quantitative phosphorylation data from cell lysates originating from primary cells, and how to analyze the generated data to construct quantitative signaling network models, are presented. These models can subsequently be used to guide follow‐up in vitro/in vivo validation studies. Curr. Protoc. Immunol . 104:11.11.1‐11.11.23. © 2014 by John Wiley & Sons, Inc.